Chroococcoid cyanobacteria Synechococcus spp. in the Black Sea: pigments, size, distribution, growth and diurnal variability - Uysal, Zahit (Journal of Plankton Research, 2001)
Phycoerythrin-containing unicellular cyanobacteria Synechococcus spp. were studied for the first time during April-May 1994 and September-October, 1996, in the western and southern Black Sea for pigments, size and abundance distribution via spectrometry, epifluorescence microscopy and flow cytometry. Abundance distribution in the surface mixed layer in April-May, 1994, revealed that cells were more concentrated in offshore waters than in coastal regions under the direct influence of the river Danube. However, in the south, higher surface cell concentrations were characteristic of the nearshore areas during September-October, 1996. A highly significant correlation was observed between cell abundance and ambient physico-chemical parameters with depth. Visual inspection of the individual cells under the epifluorescence microscope revealed that cells at the subsurface, chlorophyll a maximum layer (SCML, based on in situ fluorometer readings) fluoresce more brightly and for longer than those at the surface and at lower depths. Spectral properties of a total of 64 Synechococcus spp. clonal isolates from different depths within the euphotic layer (about the top 60 m) in the southern Black Sea coast showed that all have type 2 phycoerythrobilin in common, lacking phycourobilin. In vivo fluorescence emission maxima for phycoerythrobilin were about the same (similar to 578 nm) for all isolates. All isolates had in vivo absorption maxima at between 435 and 442 nm, and at about 681 nm due to chlorophyll a. It was shown from the flow cytometer mean forward light scatter data for size distribution that cells at the surface mixed layer (0-10 m) were larger than cells at lower depths (20-60 m). Based on in vivo fluorescence measurements, significant differences in the acclimated growth rates of clones from different depths were observed. Time versus cell count plots showed that cells of the cyanobacteria Synechococcus spp. are under grazing pressure, from midnight until noon, and slowly begin to rebuild their population in the ...